METODE PLAKSANAAN PEKERJAAN SLAB PADA JEMBATAN CILUTUNG DI KEC. TOMO KAB. SUMEDANG - Maryono; Juliar, Eka (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2023)
Cilutung Bridge is one of the bridges located on Jalan Raya Tolengas, Tolengas, Tomo District, Sumedang Regency. Bridges have various types of bridges, namely girder bridges, arch bridges, truss bridges, suspension bridges. The bridge component is divided into two, namely the superstructure and the substructure. The structure of the bridge generally includes: sidewalks, vehicle floor slabs, girders, diaphragm beams, and platforms. The structure under the bridge generally includes: the base of the bridge (abutments), bridge pillars (piers) and foundations. The bridge slab is a horizontal structural element that functions to distribute dead and live loads to the vertical support frame of a structural system. The stages of implementing the bridge slab work are 1. Preparatory work, 2. Steel bridge deck installation, 3. Steel bridge deck grouting work, 4. Cantilever slab formwork assembly, 5. Slab and parapet reinforcement assembly, 6. Cantilever slab formwork installation, 7. Check completeness and measurement, 8. Bridge slab reinforcement installation, 9. Bridge parapet reinforcement installation, 10. Bridge slab formwork installation 11. Measurement, 12. Block out deck drain installation, 13. Bridge slab floor cleaning, 14. Inspection, 15. Bridge slab casting, 16. Slump and quality check, 17. Formwork demolition work, 18. Maintenance and tidiness.